2005
DOI: 10.1007/s10406-005-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced nephropathy

Abstract: How contrast medium-induced nephropathy (CIN) comes about is not fully understood, although CIN constitutes a leading cause of renal failure. Here, a short review of clinical trials and a more thorough outline of mechanisms thought to cause CIN are outlined. Osmolality is only one of several physicochemical properties of contrast media (CM). Iso-osmolar CM are dimers, not monomers. Thus, they have physicochemical features different from other CM, e.g., in terms of viscosity (which is over fivefold greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
0
13
0
3
Order By: Relevance
“…3 In patients with preexisting renal impairment, CIN is more frequently reported, and the poorer the renal function the higher the incidence of CIN. 4 The pathophysiology of CIN is poorly understood, although hemodynamic effects, direct tubular toxicity, and oxidative stress are considered to be amongst the most important factors.…”
Section: Introductionmentioning
confidence: 99%
“…3 In patients with preexisting renal impairment, CIN is more frequently reported, and the poorer the renal function the higher the incidence of CIN. 4 The pathophysiology of CIN is poorly understood, although hemodynamic effects, direct tubular toxicity, and oxidative stress are considered to be amongst the most important factors.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping in mind that CIN only indicates a rise in serum CR and does not necessarily imply renal dysfunction, let alone renal failure, the utility of routinely performing a renal function test to identify a very small subset of patients at risk of elevating a laboratory value (CIN) is highly debatable. In fact the characterization of CIN by itself as a harbinger of more serious renal damage is doubtful since most cases have been reported to be self-limiting 15. None of our patients developed acute renal failure or required an admission for renal dysfunction.…”
Section: Discussionmentioning
confidence: 66%
“…In this regard, not so much osmolality as higher viscosity during intra-arterial injection was presumed to be a potential explanation [16,18]. On the contrary, in a recent study, the incidence of CIN following TACE of HCC seemed to be comparable to that after intra-venous contrast media administration [12].…”
Section: Discussionmentioning
confidence: 87%
“…Assessing the administered contrast material volume for both cohorts was the first priority of our study, as the prevention of CIN remains an issue of great current interest [12,17,18,20]. As we demonstrated that 4D-CTA TACE can be performed with twothirds less arterially administered contrast media volume in comparison to the standard TACE procedure, we presume that this technique might decrease the risk of CIN and may enable TACE treatment for patients with reduced renal function, although our study did not aim at investigating this end point.…”
Section: Discussionmentioning
confidence: 99%